Semi Automatic Retargeting for Facial Expressions of 3D Characters with Fuzzy logicBased on BlendshapeInterpolation - Zikky, Moh.; Hariadi, Mochamad; ., Muhtadin (Politeknik Elektronika Negeri Surabaya (PENS), 2013)
To produce a 3D virtual characters face expression of humanâs natural face expressions, facial motion capture is the technique considered to be the most effective one, especially in terms of production speed. However, there are still some results showing that the expression is not so expressive, especially on the side of the 3D character which has a different facial features than the real models regarding to the application of it. In this research, the correction of the basic expressions of faces in the process of facial motion retargeting was done by using blendshape interpolation method that was based on fuzzy logic. Blendshape interpolation method is the method used to combine multiple shapes into one blend with the concept of interpolation. In this research, the process of blendshape meets the concept of linear interpolation which the movement of a point of vertexon blendshape used straight lines . Blendshape method will be run as a proofreader on the results of retargeting process. Theweighting of blendshape will be assigned automatically from the results of the calculation of fuzzy logic, which refers to the input of the marker position of the facial motion retargeting. This weight is then used to provide improvements to create more expressive expressions. This process will be easier and faster to do than doing customize one by one at the vertex point manually. To avoid the appearance of irregular motion (haphazard movement), it is necessary to give the limitation of the weight (weight constraint) with range of [0,1].Keywords : Blendshape, retargeting, fuzzy logic, facial motion capture.